Factors Associated with the Incidence of Medication Errors and Nurses\' Refusal to Error Reporting - Hosein Ebrahimipour; Payam Mahmoudian; Elahe Hosseini; Saeed Tabatabaii; Shapour Badiee; Ali Vafaee-Najar; Hajar Haghighi (Kerman University of Medical Sciences, 2016)
Ebrahimipour Hosein1, Mahmoudian Payam2, HosseiniSeyed Elahe2, Badiee Shapour3, TabatabaeeSeyed Saeed4, VafaeeNajar Ali1, Haghighi Hajar2* Received: 16. 03. 2015             Revised: 18. 04. 2015              Accepted: 01. 07. 2015 1.Associate Professor, Department of Health Services Management, School of Public Health, Mashhad University of Medical Sciences, Mashhad, Iran. 2.MSc Student, School of Public Health, Mashhad University of Medical Science, Mashhad, Iran. 3.PhD Student, School of Public Health, Mashhad University of Medical Sciences, Mashhad, Iran. 4. Assistant Professor, School of Traditional Medicine, Mashhad University of Medical Sciences, Mashhad, Iran. *Correspondence: Mashhad, Daneshgah Avenue, Daneshgah 18, School of Public Health. Tel: 09134418276                             Email: haghighih911@mums.ac.ir Abstract Introduction: Medication errors may occur at every stage of the medicines prescription and distribution processes and as nurses can give more than 150 medicines to patients in one work shift, they are in the first line of medical errors. This study was done to investigate the factors associated with nurses' refusal to error reporting in one of the largest teaching hospitals affiliated to Mashhad University of Medical Sciences. Method: In this cross - sectional, descriptive analytic study, a medication errors questionnaire containing 66 questions was distributed among 100 nurses in different hospital departments which were selected by stratified and simple random sampling. Descriptive statistics was used to determine the most important occurred errors and the reasons for them and one way ANOVA and independent t-test were used to determine the relationship of the causes of medication errors and refusal to error reporting with nurses' demographic factors. Data were analyzed through SPSS18 software. Results: According to the obtained findings, 87.6% of nurses were female, 85.9% were married and 47.1% were circulating nurses. "Giving medicines to the patients earlier or later than the prescribed time" was the most occurred error (48.8%). "Fear of getting involved with law enforcement," was the most important cause of refusal to error reporting (3.48±1.53) and "heavy workload" was the main reason of error occurrence (4.18±1.1). Conclusion: Medication errors, however minor, can cause complications. To reduce medication errors, re-education classes in relation to pharmacological information, encouragement of nurses to report medical errors and positive reaction of head nurses are required. Keywords: Medication errors, Nursing Staff, Not Reporting, Inpatient Wards, Teaching Hospital Citation: Ebrahimipour H, Mahmoudian P, Hosseini SE, Badiee S, Tabatabaee SS, Vafaee Najar A, Haghighi H. Factors Associated with the Incidence of Medication Errors and Nurses' Refusal to Error Reporting. Journal of Health Based Research 2016; 1(3): 241-253.